Enhancing Approaches for Thriving in the Digital Economy - Jingwen, Wu; Chen Lijuan; Li Yuai (International Journal of Advances in Business and Management Research (IJABMR), 2024)
The introduction of cutting-edge digital technology has triggered a sea change in many industries, heralding a potential reconfiguration of labor dynamics, strategic approaches, and legislative frameworks. This article critically examines the dynamic nature of the digital economy, analyzing its emerging characteristics while acknowledging its persistent components. The article reveals three fundamental business techniques that constitute the foundation of its structure: modularity, open innovation, and platforms. These techniques embody the fundamental principles of organization and their significant ramifications for society. Within the context of underdeveloped countries, the digital economy brings a unique convergence of both obstacles and potential. Organizations and governmental decision-makers face the challenge of reconciling the need for innovation with the pursuit of strategic positioning. This study examines the strategic opportunities available to businesses operating in underdeveloped countries, with a particular emphasis on market dynamics and innovation. Importantly, in order to spur innovation and secure a competitive edge in the digital economy, you don’t have to be able to see whole world’s info. Several openings exist, especially in industrial applications, where physical systems and domain-specific knowledge are still necessary. Although key platform owners possess significant skills, such as data access and analysis, the ability to promote innovation and establish new market niches is not limited to them alone. The digital economy represents a fundamental change in the way economic activities are conducted, requiring individuals and organizations to possess the capacity to adapt, customize, and continuously innovate in order to fully use its capabilities.